2022
DOI: 10.5535/arm.22034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antigravity Treadmill Gait Training on Gait Function and Fall Risk in Stroke Patients

Abstract: Objective To investigate the effect of antigravity treadmill gait training (AGT) on gait function, balance, and fall risk in stroke patients.Methods This study included 30 patients with stroke (mean age, 73 years). All subjects were randomly divided into two groups. The intervention group (n=15) performed AGT for 20 minutes, five times per week for 4 weeks. The control group (n=15) received conventional gait training for the same duration. To assess fall risk, the Tinetti Performance-Oriented Mobility Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…(18) reported that LBPP was superior to the control group in balance and walking ability measured by the Berg Balance Scale, TUG, and 10MWT after four weeks of treatment in chronic stroke patients. Similarly, Oh et al (19) found that the use of an anti-gravity treadmill has been proven to be an effective intervention approach for lowering the risk of falling in stroke patients, as measured by the Tinetti Performance-Oriented Mobility Assessment, the BBS and the TUG. Sukonthamarn et al (21) and Duran et al (20) recruited acute and subacute stroke patients who were more susceptible to spontaneous recovery than the effect of the intervention (37).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…(18) reported that LBPP was superior to the control group in balance and walking ability measured by the Berg Balance Scale, TUG, and 10MWT after four weeks of treatment in chronic stroke patients. Similarly, Oh et al (19) found that the use of an anti-gravity treadmill has been proven to be an effective intervention approach for lowering the risk of falling in stroke patients, as measured by the Tinetti Performance-Oriented Mobility Assessment, the BBS and the TUG. Sukonthamarn et al (21) and Duran et al (20) recruited acute and subacute stroke patients who were more susceptible to spontaneous recovery than the effect of the intervention (37).…”
Section: Discussionmentioning
confidence: 96%
“…Sukonthamarn et al (21) and Duran et al (20) recruited acute and subacute stroke patients. Oh et al (19) and Park and Chung (18) found that LBPP improved balance and walking ability compared to the control group in chronic stroke patients.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The control performance also needs to be optimized to provide more accurate unloading force. Moreover, an optimized protocol for the proposed system needed to be investigated for future clinical use (Oh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the variation in speed and slope introduces a dynamic aspect to the rehabilitation program, challenging patients' balance and coordination in a controlled environment. This dynamic challenge is essential for retraining the neural pathways involved in gait and balance, enhancing proprioception and motor control, which are vital for preventing falls and improving walking confidence [21,22]. The purpose of this study is to delve into the impact of varying training protocols on the AGT in the rehabilitation of stroke patients, with a keen focus on the effects of speed increment training.…”
Section: Introductionmentioning
confidence: 99%